Dynamics of Transcription Factors in Three Early Phases of Osteogenic, Adipogenic, and Chondrogenic Differentiation Determining the Fate of Bone Marrow Mesenchymal Stem Cells in Rats - Zhang, Qingyu; Dong, Jun; Zhang, Peng; Zhou, Dongsheng; Liu, Fanxiao (Frontiers in Cell and Developmental Biology, 2021)
The imbalance of osteogenic, adipogenic, and chondrogenic differentiation in bone marrow mesenchymal stem cells (BMSCs) occurred in multiple age-related degenerative diseases such as osteoporosis and osteoarthritis. In order to improve our understanding and control of multi-directional differentiation of BMSCs in rats, using high-throughput sequencing, we identified key gene regulatory events in the early stages of lineage commitment. Data analysis revealed two transcription factors (TFs, Tsc22d3, and Epas1) with elevated expression throughout the initiation of differentiation (3 h), lineage acquisition (12 h), and early lineage progression (72 h) of three-directional differentiation. For osteogenic differentiation, 792, 1,042, and 638 differentially expressed genes including 48, 59, and 34 TFs were identified at three time points, respectively. Moreover, the functional analysis demonstrated that 4, 12, and 5 TFs were only differentially expressed during osteogenic differentiation at 3, 12, and 72 h, respectively, and not during other two-directional differentiation. Hopx showed enhanced expression throughout three early phases during the osteogenic differentiation but no significant change in other two-directional differentiation. A similar pattern of Gbx2 expression occurred in chondrogenic differentiation. Thus, Hopx and other early responder TFs may control the osteogenic cell fate of BMSCs and participate in the development of osteoporosis. Gbx2 and other early responder TFs should be considered in mechanistic models that clarify cartilage-anabolic changes in the clinical progression of osteoarthritis.